PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Ni Made Novi Ayu Asrini; I Dewa Putu Juwana; Ni Komang Wirasti (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
So far, teachers have used a student-centered learning approach, but there are still some teachers who use conventional learning methods which result in low student learning outcomes. The aim of this research is to improve student learning outcomes in mathematics learning through implementing the Teaching at the Right Level (TaRL) approach in class XI IPA 3 SMAN 2 Denpasar for the 2023/2024 academic year. This type of research is Classroom Action Research. This research was carried out in two cycles and each cycle consisted of 4 stages, namely planning, implementation, observation and evaluation and reflection. Data collection was carried out using observation sheets and learning outcomes tests. The research method uses quantitative descriptive data to determine the percentage of completeness of learning outcomes. The results of the research were that in Cycle I the percentage of students who completed was 63.64% then increased in Cycle II with a completion percentage of 77.27. In this way, there is an increase in student learning outcomes in Mathematics learning by implementing the Teaching at The Right Level (TaRL) approach in class XI IPA 3 SMAN 2 Denpasar for the 2023/2024 academic year.